Extra long Argentinian lockdown: Revising the energy regime - Ise, Alejandra (2020)
In Argentina, goals towards protecting the environment and reducing Green House Gas emissions, within the context of an energy transition, have been relegated to the health emergency introduced by the COVID-19 outbreak. Mandatory isolation measures impacted on the energy system: they modified energy demand and production patterns, and caused reasons for uncertainty among investors and project stakeholders. Nevertheless, profound changes caused by the pandemic, pave the way for the adoption of sustainable solutions with the potential to improve people?s quality of life. This paper aims to explore the effects of the COVID-19 lockdown on the Argentinian energy sector and its repercussions on the course of the transition. By means of secondary sources, such as public reports and national statistics, and semi-structured interviews, changes in the energy sector are analysed as well as local-scale alternatives for the post-pandemic. Community-led energy initiatives and the possibility of implementing sustainable practices, could contribute to reducing uncertainty and valorizing local resources and capabilities.